Characterization of a cytochrome P450 monooxygenase capable of high molecular weight PAHs oxidization from Rhodococcus sp. P14. Issue 12 (December 2016) - Luo, An; Wu, Yi-Rui; Xu, Yan; Kan, Jie; Qiao, Jing; Liang, Lei; Huang, Tongwang; Hu, Zhong
Graphical abstract: Highlights: PAHs can induce the transcription of gene cyp108j1 . CYP108J1 initialize PAHs oxidization only with its own electron transport system. Metabolites were detected by using CYP108J1 on the treatment of different PAHs. Abstract: Rhodococcus sp. P14 is able to degrade a wide range of polycyclic aromatic hydrocarbons (PAHs). By analyzing its whole genome sequence, a gene cluster encoding cytochrome P450 monooxygenase (CYP108J1) with ferredoxin (fdx) and ferredoxin reductase (hcaD) relating to polycyclic aromatic hydrocarbons degradation was predicted. Protein sequence analysis of CYP108J1 showed 47.9% and 36.4% identity to the CYP108A1 and CYP108D1 from Pseudomonas sp. and N. aromaticivorans DSM12444 in CYP108 family, respectively. The transcriptional level of gene cyp108j1 was up-regulated when the strain was grown within the medium containing benz[a]anthracene, pyrene, phenanthrene and anthracene as the sole carbon source, and the increment was detected to be 2.4, 8.0, 16.0 and 11.3-fold, respectively, by comparing to that grown with glucose. Further investigation on the recombinant protein CYP108J1 in E. coli also indicates that CYP108J1 was capable of degrading a series of PAHs compounds (from low to high molecular weight), including biphenyl, phenanthrene, anthracene and benz[a]anthracene.